Recruitment and effectiveness by cohort in a case management intervention among American Indians and Alaska Natives with diabetes. Issue 4 (3rd July 2018) - Pratte, Katherine A; Beals, Janette; Johnson, Ann; Bullock, Ann; Manson, Spero M; Jiang, Luohua; ,
Abstract : Patient characteristics and intervention effectiveness of a diabetes management intervention program change with recruitment year. Those who were recruited later were less motivated and made fewer improvements in their intervention outcomes. Abstract: In real-world settings, eligible populations and intervention effectiveness for a translational intervention likely vary across time. To determine the optimal strategies for effective large-scale implementation of evidence-based interventions, it is critical to investigate these potential variabilities. The purpose of this study is to evaluate whether patient characteristics and intervention effectiveness differed by year of enrollment in a multiyear evidence-based translational intervention. The Special Diabetes Program for Indians Healthy Heart (SDPI-HH) Demonstration Project is an intensive case management intervention designed to reduce cardiovascular disease risk among American Indians and Alaska Natives with diabetes. SDPI-HH participants recruited from 2006 through 2008 were included. Baseline characteristics were compared by year of enrollment. We also evaluated the differences in improvements in clinical and behavioral risk factors for cardiovascular disease among participants recruited in different years. The baseline characteristics of the three cohorts significantly differed in demographics, diabetes duration, health behaviors, level of motivation, and clinical measures. Improvements in 13 clinical and behavioral outcomes also differed by enrollment year with the 2006 cohort having the greatest number of significant improvements and the highest rates of participation and retention. Further investigation into the ways to modify the intensive case management model to address differences in levels of motivation and participation is warranted to improve the management of chronic disease in Indian health. Given the evolving nature of translational initiatives of this kind, our analysis results highlight the need to understand and adapt during the natural progression of health behavioral interventions.